PERAN BALAI LATIHAN KERJA DALAM MENINGKATKAN KUALITAS TENAGA KERJA SEBELUM MEMASUKI DUNIA KERJA DI UNIT PELAKSANA TEKNIS DAERAH BALAI LATIHAN KERJA (UPTD BLK) PADANG PARIAMAN - Adrianto; Sumiarti, Tati; Bahri, Muhammad Emirul; Karisha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the importance of improving the quality of the workforce in facing competition in the world of work by providing training that will improve people's abilities carried out by job training centers. The aim of this research is to find out the role of job training centers in improving the quality of the workforce before entering the world. works at UPTD BLK Padang Pariaman. The research method used is qualitative research with a descriptive approach. Data collection techniques were carried out through observation, in-depth interviews with analysis techniques in the form of data reduction, data display and conclusions. The results of this research indicate that the role of UPTD BLK Padang Pariaman has been running well, but has not been optimal in improving the quality of the workforce, due to heterogeneous participants, inadequate training equipment, limited number of instructors and budget received and the absence of placement or distribution of work.